PENGAWETAN LIMA JENIS KAYU SECARA PELABURAN MEMAKAI DUA JENIS BAHAN PENGAWET - Sasa Abdurrohim (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Five air dried timber species measured 2.5 x 5 x 10 cm was brushed by preservative in one of the broader side for four, seven and ten times which similar with 1.25 g, 1.75 g and 2.25 g preservative. The preservative used were Xylamon 5. 61 OC and Cuprinol 118 L, with the replication per treatment were ten. Two weeks after treatment preservative penetration in all samples was measured.The results showed that the preservative penetration of all treatment did not mee trequirements for timber housing. Additional brushing may be could improve penetration and meet the standard but it will be costly. The cost offour, seven and ten times brushing if appliedin door frame are Rp 245,530,- Rp. 343,742,- and Rp. 44J,953,- per m3 with the price of preservative Rp. 13,500,- per liter.Key words: brushing, Xylamon, Cuprinol, penetration